Cancer Stem Cells: Targeting the Roots of Cancer, Seeds of Metastasis, and Sources of Therapy Resistance - Adorno-Cruz, Valery (Cancer Res, 2015)
With the goal to remove the roots of cancer, eliminate metastatic seeds, and overcome therapy resistance, the 2014 inaugural International Cancer Stem Cell (CSC) Conference at Cleveland, OH, convened together over 320 investigators, including 55 invited world-class speakers, 25 short oral presenters, and 100 poster presenters, to gain an in-depth understanding of CSCs and explore therapeutic opportunities targeting CSCs. The meeting enabled intriguing discussions on several topics including: genetics and epigenetics; cancer origin and evolution; microenvironment and exosomes; metabolism and inflammation; metastasis and therapy resistance; single cell and heterogeneity; plasticity and reprogramming; as well as other new concepts. Reports of clinical trials targeting CSCs emphasized the urgent need for strategically designing combinational CSC-targeting therapies against cancer.